Empacotamento de experimentos controlados em engenharia de software: uma abordagem baseada em ontologia - Scatalon, Lilian Passos [UNESP] (2013)
Experimental Software Engineering attempts to assess the performance of methods, techniques and tools applied on software development activities. The goal is to build a body of experimentally validated knowledge in order to support decision making on Software Engineering domain. Building this body of knowledge requires to run controlled experiments and their replications in order to generalize the obtained results. The information and the knowledge generated by an experiment are registered in the so-called lab package, which must be reviewed by an eventual research group with the intention to replicate it. However, researchers face difficulties while reviewing the available lab packages. One of the factors that leads to this problem is the lab packages lack of standardization. The experiments are reported with different information sets, what is also a barrier to integrate studies in a common body. In this context, considering that knowledge sharing and integration are recurring applications of ontologies, in this work is proposed a workflow that applies an ontology to package controlled experiments in Software Engineering. In order to evaluate this approach, the tool Ponto- Lab++ was implemented, which corresponds to a workflow instance that adopts EXPEROntology, an ontology for controlled experiments